ANALISIS STRATEGI KOMUNIKASI PEMASARAN DIGITAL AKUN INSTAGRAM @dr. VEE CLINIC SEBAGAI MEDIA KEBUTUHAN INFORMASI KECANTIKAN - Vivi, Sondang Rita; Shasrini, Tessa (Telangke:Jurnal Telangke Ilmu Komunikasi, 2023)
In the current era of technological development, business in the field of beauty has greatly increased its demand. Coupled with the massive information received by the public through social media, beauty clinics compete with each other to highlight their respective advantages. With lots of business competition with other beauty clinics, the right marketing communication strategy can help companies face the competition. Coupled with the use of social media Instagram in promoting the clinic dr. Vee. The purpose of this research is to find out what digital marketing strategies are used by Dr. Vee. This study uses AIDA theory to measure the effectiveness of promotions and messages conveyed. Using descriptive qualitative research methods with data collection methods through interviews, observation, documentation. The number of subjects in this study amounted to 5 people, namely the owner of dr. Vee Clinic, admin & marketing dr. Vee Clinic and 3 other people who use dr. Vee. The results of the qualitative analysis show that the use of the marketing communication mix is ​​very effective in attracting enthusiasts and social media facilitates the dissemination of information.